Transcription of human resistin gene involves an interaction of Sp1 with peroxisome proliferator-activating receptor gamma (PPARgamma). - Anil K Singh (Public Library of Science (PLoS), 2010)
Background Resistin is a cysteine rich protein, mainly expressed and secreted by circulating human mononuclear cells. While several factors responsible for transcription of mouse resistin gene have been identified, not much is known about the factors responsible for the differential expression of human resistin. Methodology/principal finding We show that the minimal promoter of human resistin lies within approximately 80 bp sequence upstream of the transcriptional start site (-240) whereas binding sites for cRel, CCAAT enhancer binding protein alpha (C/EBP-alpha), activating transcription factor 2 (ATF-2) and activator protein 1 (AP-1) transcription factors, important for induced expression, are present within sequences up to -619. Specificity Protein 1(Sp1) binding site (-276 to -295) is also present and an interaction of Sp1 with peroxisome proliferator activating receptor gamma (PPARgamma) is necessary for constitutive expression in U937 cells. Indeed co-immunoprecipitation assay demonstrated a direct physical interaction of Sp1 with PPARgamma in whole cell extracts of U937 cells. Phorbol myristate acetate (PMA) upregulated the expression of resistin mRNA in U937 cells by increasing the recruitment of Sp1, ATF-2 and PPARgamma on the resistin gene promoter. Furthermore, PMA stimulation of U937 cells resulted in the disruption of Sp1 and PPARgamma interaction. Chromatin immunoprecipitation (ChIP) assay confirmed the recruitment of transcription factors phospho ATF-2, Sp1, Sp3, PPARgamma, chromatin modifier histone deacetylase 1 (HDAC1) and the acetylated form of histone H3 but not cRel, C/EBP-alpha and phospho c-Jun during resistin gene transcription. Conclusion Our findings suggest a complex interplay of Sp1 and PPARgamma along with other transcription factors that drives the expression of resistin in human monocytic U937 cells.